Development of a Roadmap for the Implementation of a Sustainable Mobility Action Plan in University Campuses of Emerging Countries - Tormo-Lancero, María Teresa; Valero-Mora, Pedro; Sanmartin, Jaime; Sánchez-García, Mar; Papantoniou, Panagiotis; Yannis, George; Alonso, Francisco; Campos-Díaz, Eva (Frontiers in Sustainable Cities, 2022)
Universities are centers of knowledge and their Campuses are like small cities, thus making them the ideal place to develop, apply and evaluate policies and tools for innovative mobility solutions that can subsequently be extended to other contexts. A review of mobility measures in different European Universities has revealed that many of them apply policies to promote sustainable mobility, but there is a significant lack of standardized mobility plans and roadmaps for their successful implementation. The objective of the present work is to develop a successful roadmap, which is necessary for the smooth implementation of a mobility plan, as it has been found through a thorough review of good practices in Universities. Within this framework, a customizable standardized Roadmap design is proposed, which consists of two documents: a tactical document that provides a global and sequential vision of the entire plan, and an operational document that details the actions for each strategic line. This roadmap is accompanied by a catalog of objectives, measures, and cost and impact indicators. We consider this design instructive for universities because of its universal characteristics in Emerging Countries. To ensure this, it is necessary to apply this roadmap and carry out the corresponding evaluation.